2014
DOI: 10.1002/cae.21609
|View full text |Cite
|
Sign up to set email alerts
|

A realistic generator of power quality disturbances for practicing in courses of electrical engineering

Abstract: This paper presents a realistic generator of power quality (PQ) disturbances developed using real time-hardware in the loop (RT-HIL) technologies; the aim is to reduce the gap between the PQ mathematical theory and its practical application by improving the technical skills of students through the use of instruments in a controlled and safe laboratory environment. The implementation of this interactive teaching tool in a graduate level course has significantly enhanced the communication process between the tea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
36
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(37 citation statements)
references
References 16 publications
1
36
0
Order By: Relevance
“…Additionally, students indicated that the intended course objectives were accomplished and that there was a good level of satisfaction. These opinions are similar to those obtained by other similar studies demonstrating the effectiveness of FPGA‐based systems in engineering courses .…”
Section: Discussionsupporting
confidence: 90%
“…Additionally, students indicated that the intended course objectives were accomplished and that there was a good level of satisfaction. These opinions are similar to those obtained by other similar studies demonstrating the effectiveness of FPGA‐based systems in engineering courses .…”
Section: Discussionsupporting
confidence: 90%
“…The simulation of power harmonics (or systems with harmonic distortion) has also been explicitly considered as a learning outcome by several authors . This can be accompanied by the need to know how to set simulation parameters [39,46]. Other less common learning outcomes are the ability to acquire or monitor power harmonics and relate theoretical principles to real‐life observations of this distortion [3,46].…”
Section: Resultsmentioning
confidence: 99%
“…This can be accompanied by the need to know how to set simulation parameters [39,46]. Other less common learning outcomes are the ability to acquire or monitor power harmonics and relate theoretical principles to real‐life observations of this distortion [3,46]. Several authors treat harmonic distortion indirectly: they want students to have the ability to model power electronics systems (PV systems, converters, etc.)…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations